"Created this way": liminality, rhetorical agency, and the transformative power of constraint among gay Christian college students. Issue 1 (2nd January 2017) - Gardner, Christine J.
ABSTRACT: This study offers liminality as an analytic tool to investigate the discursive strategies of the negotiation of oppositional identities. Interviews with lesbian, gay, bisexual, transgender, and queer/questioning Christian college students reveal appeals to essentialism, labeling, and identification. Specific findings include appeals to being "created gay, " the naming of identity labels that support and resist both traditional sexual minority and religious labels, and the deployment of a gay Christian identity as evangelism. This essay explores how disciplinary rhetorics create the conditions for the emergence of rhetorical agency, allowing for a nuanced understanding of the transformative possibilities of minority sexual identity formation.